Radiosynthesis and evaluation of a fluorine-18 radiotracer [18F]FS1P1 for imaging sphingosine-1-phosphate receptor 1. Issue 5 (14th January 2022) - Qiu, Lin; Jiang, Hao; Yu, Yanbo; Gu, Jiwei; Wang, Jinzhi; Zhao, Haiyang; Huang, Tianyu; Gropler, Robert J.; Klein, Robyn S.; Perlmutter, Joel S.; Tu, Zhude
Abstract : A promising sphingosine-1-phosphate receptor 1 PET radiotracer [ 18 F]FS1P1 was synthesized using a facile multiple step F-18 radiochemistry procedure. Abstract : Assessment of sphingosine-1-phosphate receptor 1 (S1PR1) expression could be a unique tool to determine the neuroinflammatory status for central nervous system (CNS) disorders. Our preclinical results indicate that PET imaging with [ 11 C]CS1P1 radiotracer can quantitatively measure S1PR1 expression changes in different animal models of inflammatory diseases. Here we developed a multiple step F-18 labeling strategy to synthesize the radiotracer [ 18 F]FS1P1, sharing the same structure with [ 11 C]CS1P1 . We explored a wide range of reaction conditions for the nucleophilic radiofluorination starting with the key ortho -nitrobenzaldehyde precursor 10 . The tertiary amine additive TMEDA proved crucial to achieve high radiochemical yield of ortho -[ 18 F]fluorobenzaldehyde [ 18 F]12 starting with a small amount of precursor. Based on [ 18 F]12, a further four-step modification was applied in one-pot to generate the target radiotracer [ 18 F]FS1P1 with 30–50% radiochemical yield, >95% chemical and radiochemical purity, and a high molar activity (37–166.5 GBq μmol −1, decay corrected to end of synthesis, EOS). Subsequently, tissue distribution of [ 18 F]FS1P1 in rats showed a high brain uptake (ID% g −1 ) of 0.48 ± 0.06 at 5 min, and bone uptake of 0.27 ± 0.03, 0.11 ± 0.02 at 5, and 120 min respectively, suggesting no in vivo defluorination. MicroPET studies showed [ 18 F]FS1P1 has high macaque brain uptake with a standard uptake value (SUV) of ∼2.3 at 120 min. Radiometabolite analysis of macaque plasma samples indicated that [ 18 F]FS1P1 has good metabolic stability, and no major radiometabolite confounded PET measurements of S1PR1 in nonhuman primate brain. Overall, [ 18 F]FS1P1 is a promising F-18 S1PR1 radiotracer worthy of further clinical investigation for human use.